Hubungan Dukungan Keluarga dengan Pemenuhan Personal Hygine pada Pasien Stroke yang Mengalami Gangguan Mobilitas Fisik - Alif Sahilah; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
stroke causes physical mobility disorders, having an impact on the patient's ability to personal hygiene. This study aims to analyze the relationship between family support and the fulfillment of personal hygiene needs in stroke patients who experience physical mobility disorders. a type of quantitative research, using an observational analytical design of a cross-sectional approach. Purposiv sampling technique. The number of sample was 113 people to 88 respondents. The research instrument used a family and personal hygine support questionnaire bivariate analysis test with gamma coefficient test obtained a p value of 0.001, ,a coefis value . Personal hygiene in stroke patients who experience impaired physical mobility. The higher the family support, the higher the fulfillment of personal hygiene needs in stroke patients.